2011
DOI: 10.7150/ijbs.7.112
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Method (FEM), Mechanobiology and Biomimetic Scaffolds in Bone Tissue Engineering

Abstract: Techniques of bone reconstructive surgery are largely based on conventional, non-cell-based therapies that rely on the use of durable materials from outside the patient's body. In contrast to conventional materials, bone tissue engineering is an interdisciplinary field that applies the principles of engineering and life sciences towards the development of biological substitutes that restore, maintain, or improve bone tissue function. Bone tissue engineering has led to great expectations for clinical surgery or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 135 publications
(156 reference statements)
1
99
0
Order By: Relevance
“…When a bone defect reaches a certain range, no new bone forms through the normal physiological healing process; this is considered a critical bone defect 19) . The practical signifi cance of this to bone tissue engineering is that when a critical bone defect occurs, new bone can be induced by introduction of a biological scaffold seeded with cells and loaded with growth factors to regenerate the bone defect 39) . During bone formation, the scaff old is degraded continuously, and the product is not biologically toxic.…”
Section: Discussionmentioning
confidence: 99%
“…When a bone defect reaches a certain range, no new bone forms through the normal physiological healing process; this is considered a critical bone defect 19) . The practical signifi cance of this to bone tissue engineering is that when a critical bone defect occurs, new bone can be induced by introduction of a biological scaffold seeded with cells and loaded with growth factors to regenerate the bone defect 39) . During bone formation, the scaff old is degraded continuously, and the product is not biologically toxic.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a number of hypotheses exist for predicting the formation of different tissue types (for example, bone, cartilage and connective tissue) under different mechanical stimulation protocols and magnitudes in vivo. Recent reviews of mathematical models based on these hypotheses may be found in Isaksson (2012) and Boccaccio et al (2011). It is an open question whether the hypotheses proposed are valid for in vitro tissue engineering studies (Khayyeri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate biophysical stimuli are needed in bone scaffolds, in addition to nutrients and appropriate levels of oxygen supply, to favour an appropriate tissue differentiation process (Martin et al, 2004. A number of studies (Byrne et al, 2007, Milan et al, 2009Olivares et al, 2009, Sanz-Herrera et al, 2009) are reported in literature that through a combined use of finite element method and mechano-regulation algorithms described the possible patterns of the tissues differentiating within biomimetic scaffolds for tissue engineering (Boccaccio et al, 2011a). In this Chapter we will focus on the first domain of applicability (i) and, specifically, two examples will be illustrated that show how mechanobiology can be used to predict the patterns of tissue differentiation in a human mandible osteotomized and submitted to distraction osteogenesis as well the regrowth and the remodelling process of the cancellous bone in a vertebral fracture.…”
Section: Mechanobiology: Domains Of Applicabilitymentioning
confidence: 99%